DOI: 10.18174/400833
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the productivity of cassava in West Africa

Abstract: Drought stress and sub-optimal soil fertility management are major constraints to crop production in general and to cassava (Manihot esculenta Crantz) in particular in the rain-fed cropping systems in West Africa. Cassava is an important source of calories for millions of smallholder households in sub-Sahara Africa. The prime aim of this research was to understand cassava productivity in order to contribute to improving yields, food security and farm incomes in rain-fed cassava production systems in West Afric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…Because farmers can obtain roots for their subsistence from cassava planted on very marginal fields [56][57][58], a low-to-no input farming system is preferred compared to an input-intensive farming system for cassava. The slash and burn system that is still practiced by some Zambian farmers, especially in the Northern part of the country [59], could also explain the observed low fertilizer use in Zambia.…”
Section: Fresh and Dry Cassava Root And Biomass Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Because farmers can obtain roots for their subsistence from cassava planted on very marginal fields [56][57][58], a low-to-no input farming system is preferred compared to an input-intensive farming system for cassava. The slash and burn system that is still practiced by some Zambian farmers, especially in the Northern part of the country [59], could also explain the observed low fertilizer use in Zambia.…”
Section: Fresh and Dry Cassava Root And Biomass Yieldmentioning
confidence: 99%
“…The slash and burn system that is still practiced by some Zambian farmers, especially in the Northern part of the country [59], could also explain the observed low fertilizer use in Zambia. However, as evidenced in West and East African countries [56,58,60], a low input production system cannot support the high crop yield required to meet the needs of a growing population and can also cause environmental degradation, through deforestation and carbon dioxide emissions. Therefore, these conditions necessitate the use of fertilizer, either organic or mineral sources, to sustain cassava farming in the long run and meet the growing cassava demand in the country.…”
Section: Fresh and Dry Cassava Root And Biomass Yieldmentioning
confidence: 99%
“…The largest cassava yield of 35 t DM ha -1 at 14 MAP was achieved in Edo, equivalent to 97 t ha -1 of fresh storage roots. No effects of drought were observed in 2016 for Edo, despite a brief dry season, due to the rooting depth of cassava in this field, which was greater than 3.2 m. This observed yield is larger than the target yield of 90 t ha -1 of fresh roots which we used to determine the nutrient requirements with the QUEFTS model (Ezui, 2017). These yields are comparable to the simulated ideal yield of 32 t DM ha -1 at 12 MAP proposed by Cock et al (1979) and to the actual recorded yields of 27 -32 t DM ha -1 at 10 MAP reported from Cauca, Colombia (El-Sharkawy et al, 1990).…”
Section: Nutrient Harvest Index (Nhi)mentioning
confidence: 67%
“…Treatment names are as shown in Table 2.2, where (f) represents full rate of the optimized nutrient and K60, K120, K180, K240, were varied at rates of K at 60, 120, 180 and 240 kg ha -1 (Table 2.2). The optimized fertilizer rates and combinations for the experimental treatments were determined using the Quantitative Evaluation of the Fertility of Tropical Soils (QUEFTS) model for cassava (Ezui, 2017), aiming at a yield of 90 t fresh roots ha -1 (equivalent to 32 t DM ha -1 ). Cassava variety TME 419 was grown in all experiments: this is a popular variety in Nigeria and West Africa because it has high dry matter and is nutrient use efficient (De Souza and Long 2018).…”
Section: Experimental Treatments and Managementmentioning
confidence: 99%
See 1 more Smart Citation